Rituximab for the treatment of connective tissue disease-associated interstitial lung disease - Chartrand, Sandra; Swigris, Jeffrey J; Peykova, Lina; Fischer, Aryeh (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Objective: To describe our experience with rituximab (RTX) as treatment for a diverse spectrum of chronic connective tissue disease-associated interstitial lung disease (CTD-ILD). Methods: Twenty-four subjects with CTD-ILD were included. All had pulmonary function testing before and after their first RTX infusion. Each subject was evaluated in a multidisciplinary autoimmune and ILD outpatient clinic. Data were extracted by retrospective review of complete medical records. Results: Most subjects were middle-aged white women with rheumatoid arthritis (RA) (n=15) and a nonspecific interstitial pneumonia (NSIP) pattern on high-resolution chest computed tomography scans (n=17). Sixteen subjects received a corticosteroid-sparing agent at the time of RTX initiation; mostly mycophenolate mofetil (n=8). RTX administration was not associated with corticosteroid-sparing effects: 13 subjects were on prednisone at the time of the initial RTX cycle, and 9 remained on prednisone at 6 months after (mean daily dosage 10.2±16.2 mg before vs. 5.6±11.0 mg after, p=0.27). RTX had no appreciable effect on pulmonary physiology; however, individual trajectories for percentage predicted forced vital capacity (FVC%) were highly variable. The underlying CTD (RA vs. non-RA) and ILD pattern did not appear to affect response to RTX. Among 14 subjects who received multiple RTX cycles, FVC% trajectories were variable: FVC% increased in eight and declined in six. Respiratory infections were the most common post-RTX adverse event. Conclusion: In this small, retrospective study of chronic CTD-ILD, RTX was not associated with changes in FVC% or corticosteroid-sparing effects. Controlled, prospective studies are needed to more confidently define the effects of RTX in CTD-ILD. (Sarcoidosis Vasc Diffuse Lung Dis 2015; 32: 296-304)